2018
DOI: 10.1038/s41419-018-0843-z
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 regulates WTAP protein homeostasis

Abstract: The Wilms tumor 1 (WT1)-associated protein (WTAP) is upregulated in many tumors, including, acute myeloid leukemia (AML), where it plays an oncogenic role by interacting with different proteins involved in RNA processing and cell proliferation. In addition, WTAP is also a regulator of the nuclear complex required for the deposition of N6-methyladenosine (m6A) into mRNAs, containing the METTL3 methyltransferase. However, it is not clear if WTAP may have m6A-independent regulatory functions that might contribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 29 publications
4
97
0
1
Order By: Relevance
“…Similar results were also found in lung cancer [58]. It was also demonstrated that cytoplasmic METTL3 can promote translation of specific mRNAs independently from its catalytic activity [54,58]. Moreover, higher levels of cytoplasmic METTL3 results in concomitant increase of WTAP protein expression [54].…”
Section: M6a Roles In Aml (Acute Myeloid Leukaemia) and Normal Haesupporting
confidence: 59%
“…Similar results were also found in lung cancer [58]. It was also demonstrated that cytoplasmic METTL3 can promote translation of specific mRNAs independently from its catalytic activity [54,58]. Moreover, higher levels of cytoplasmic METTL3 results in concomitant increase of WTAP protein expression [54].…”
Section: M6a Roles In Aml (Acute Myeloid Leukaemia) and Normal Haesupporting
confidence: 59%
“…Epigenetic imprinting through DNA methylation (7)(8)(9), microRNAs (10,11), and noncoding RNAs (12) play important roles in preadipocytes adipogenesis. N 6 -methyladenosine (m 6 A) is the most prevalent chemical modification in eukaryotic mRNA (13), and it is installed by the methyltransferase complex mainly consisting of the methyltransferase-like (METTL)3-METTL14-WTAP core, which are essential components with catalytic and structural functions, respectively (14)(15)(16). However, this process could be reversed by fat mass and obesity-associated protein (FTO) (17) or AlkBH5 (18).…”
mentioning
confidence: 99%
“…Recently, more and more studies have suggested that the abnormal expression of the m 6 A RNA methylation regulators is involved in human cancer. The writer WTAP was reported to be a oncogene in different cancers, such as AML (38), glioblastoma (39), and pancreatic ductal adenocarcinoma (40). The eraser ALKBH5 was observed to be up regulated in glioblastoma stemlike cell (GSCs), leading to the initiation and development of glioblastoma (41).…”
Section: Discussionmentioning
confidence: 99%